The Generated Entropy Monitored by Pyroelectric Sensors - Hsiao, Chun-Ching (Sensors (Basel), 2018)
Entropy generation in irreversible processes is a critical issue that affects the failure and aging of electrical, chemical or mechanical systems. The promotion of energy conversion efficiency needs to reduce energy losses, namely to decrease entropy generation. A pyroelectric type of entropy detector is proposed to monitor energy conversion processes in real time. The entropy generation rate can be derived from the induced pyroelectric current, temperature, thermal capacity, pyroelectric coefficient and electrode area. It is profitable to design entropy detectors to maintain a small thermal capacity while pyroelectric sensors minimize geometrical dimensions. Moreover, decreasing the electrode area of the PZT cells could avoid affecting the entropy variation of the measured objects, but the thickness of the cells has to be greatly reduced to promote the temperature variation rate and strengthen the electrical signals. A commercial capacitor with a capacitance of 47 μF and a maximum endured voltage of 4 V were used to estimate the entropy to act as an indicator of the capacitors’ time-to-failure. The threshold time was evaluated by using the entropy generation rates at about 7.5 s, 11.25 s, 20 s and 30 s for the applied voltages of 40 V, 35 V, 30 V and 25 V respectively, while using a PZT cell with dimensions of 3 mm square and a thickness of 200 μm.